Childhood Trauma and Mental Health Status in General Population: A Series Mediation Examination of Psychological Distress in COVID-19 Pandemic and Global Sleep Quality - Xie, Min; Tang, Yiguo; Zhu, Ling; Dai, Minhan; Wu, Yulu; Huang, Yunqi; Liu, Yunjia; Xiao, Liling; Li, Tao; Wang, Qiang (Frontiers in Psychiatry, 2021)
Background: Coronavirus-2019 (COVID-19) has been coexisting with humans for almost two years, consistantly impacting people’s daily life, medical environment, and mental health. This study aimed to test the series mediation model triggered by childhood trauma, in which perceived psychological impact of COVID-19 pandemic and sleep quality mediated the path sequentially and led to adverse mental health outcomes. Methods: A cross-sectional design involving 817 participants were enrolled via WeChat online survey. Participants completed questionnaires, including demographic features, the Childhood Trauma Questionnaire, Impact of Event Scale‑Revised (IES‑R) questionnaire, Pittsburgh Sleep Quality Index questionnaire and Depression, Anxiety and Stress Scale (DASS‑21). Pearson correlations and hierarchical multiple linear regression were employed to examine the association of childhood trauma and psychological stress of COVID-19, sleep quality and mental health status. In addition, a series mediate anlysis was carried out to examine sequence mediating effects of psychological impact of COVID-19 and sleep quality between childhood trauma and mental health status. Results: The results showed that childhood trauma is positively and significantly related to psychological distress of COVID-19 pandemic, sleep quality and mental health status (p < 0.05). Hierarchical multiple linear regression analysis shown that demographic features explained 4.4%, 2.1% and 4.0% of the total variance in DASS-21, IES-R and PSQI total scale scores, respectively. Adding childhood trauma significantly increased the model variance of DASS-21 (∆R2 = 0.129, F = 126.092, P = 0.000), IES-R (∆R2 = 0.062, F = 54.771, P = 0.000) and PSQI total scale scores (∆R2 = 0.055, F = 48.733, P = 0.000), respectively. Moreover, the series mediation model showed that the perceived impact of the COVID-19 pandemic and sleep quality were sequential mediators between childhood trauma and mental health status (proportion explained: 49.17%, p < 0.05). Conclusion: Amid the ravages of COVID-19, childhood trauma predicts poor mental health status, in part because of greater psychological impact related to COVID-19 and poorer global sleep quality. In order to improve mental health, future researchers should pay more attention to individuals with childhood trauma, for its association with greater stress related to life events and poorer sleep quality.